2014
DOI: 10.1002/jso.23791
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary breast cancer syndromes and genetic testing

Abstract: Only 5% of breast cancers are explained by highly penetrant multisystem autosomal dominant hereditary disorders. Though another 20-30% has a familial presentation, the genetic and other etiologies are still not well understood. Genetic testing is now widely available and multiple professional societies have published guidelines for testing and management. Genetic testing trends include utilization of multi-gene panels that take advantage of next-generation sequencing as well as testing for low- and moderate-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 301 publications
(380 reference statements)
0
18
0
4
Order By: Relevance
“…In women with BC, about 1 in 10 cases represents a form of hereditary BC (Fig. 3) 61,62 ; however, in young patients, this genetic susceptibility may be higher. Predisposing gene mutations can be classified according to the relative risk (RR) of developing cancer when a patient carries a particular germline mutation.…”
Section: Germline Genomic Profile In Ywbc Bc-predisposing Gene Mutationsmentioning
confidence: 99%
“…In women with BC, about 1 in 10 cases represents a form of hereditary BC (Fig. 3) 61,62 ; however, in young patients, this genetic susceptibility may be higher. Predisposing gene mutations can be classified according to the relative risk (RR) of developing cancer when a patient carries a particular germline mutation.…”
Section: Germline Genomic Profile In Ywbc Bc-predisposing Gene Mutationsmentioning
confidence: 99%
“…These data were quickly replicated by other groups using additional sets of families [111][112][113][114]. Furthermore, systematic screening for BRCA1 and BRCA2 mutations revealed that approximately 5% of total breast cancer morbidity, and about 15-25% of familial BC clustering, is attributed to BRCA1/2 mutations [115][116][117][118][119][120]. Although the frequencies of BRCA1 and BRCA2 defects vary between different ethnic groups, with increased prevalence of BRCA1 in some and BRCA2 in others, these genes appear to have a worldwide medical significance [121].…”
Section: Breast Cancermentioning
confidence: 95%
“…Ungefähr 5 % aller Mammakarzinome können auf eine autosomaldominant vererbte genetische Erkrankung zurückgeführt werden [17]. Für die vererbbare Variante des Mammakarzinoms sind vorrangig Mutationen in den Genen BRCA1 und BRCA2 (breast cancer 1 bzw.…”
Section: Genetikunclassified